2014
DOI: 10.5817/bse2014-1-9
|View full text |Cite
|
Sign up to set email alerts
|

Researching the research article in Cameroon English

Abstract: This contribution discusses three variables of structure, citation practice, and role relationships in research articles in Cameroon English, within the background of conventional practice in the discourse community. Data is taken from 40 papers published in 7 issues of 4 journals from two state universities in Cameroon; and corroborated with a similar database from three universities in Europe. Findings indicate that articles written by Cameroonian academics display a number of differences from what is known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…This may elucidate their overemphasis in the editing process. Additionally, as pointed out by Hill, Soppelsa, and West (), and Nkemleke (), the central foci of research papers are mostly stated in introduction and discussion sections as they usually adopt a broad view, linking and discussing the previous studies in the field to the study at hand. These two sections are, thus, slots in an RA where the highest uses of citations are required.…”
Section: Discussionmentioning
confidence: 99%
“…This may elucidate their overemphasis in the editing process. Additionally, as pointed out by Hill, Soppelsa, and West (), and Nkemleke (), the central foci of research papers are mostly stated in introduction and discussion sections as they usually adopt a broad view, linking and discussing the previous studies in the field to the study at hand. These two sections are, thus, slots in an RA where the highest uses of citations are required.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the question catches a lot of attention, and the variations are treated quite differently. A striking common feature shared by Yes/No questions and wh-questions is the absence of movement transformations as is the case in standard BrE (Anchimbe 1998;Nkemleke 2007;Mbangwana and Sala 2009;Mbufong 2013;Epoge 2016b). In other words, the question is structured as a mere declaration with a final question mark (in writing) or final rinsing tone (in speech).…”
Section: Question Formationmentioning
confidence: 95%
“…In spite of these odds, a number of scholars have taken up the challenge to describe findings in the variations observed that can be considered not errors or shifts, but distinguishing morphological and syntactic features of emerging Englishes. Such endeavours have been reported in academic dissertations and theses (like Daode 2001;Fokam Tchoupo 2013), articles (such as Buregeya 2001;Schmied 2008;Nkemleke 2007; Akinlontan 2016), and books (for example, Blair and Collins 2001; Kachru and Nelson 2006;Mesthrie, Rajend & Bhatt 2008). Devoting a whole book to this effect as Mbangwana and Sala (2009) and Jowitt (2019) have done for Cameroon English (henceforth CamE) and Nigerian English (henceforth NigE), respectively, marks a significant step forward in the description and codification process of these two varieties.…”
Section: Introductionmentioning
confidence: 94%